The impact of using standardized patients in psychiatric cases on the levels of motivation and perceived learning of the nursing students. (April 2017) - Sarikoc, Gamze; Ozcan, Celale Tangul; Elcin, Melih
Abstract: Background: The use of standardized patients is not very common in psychiatric nursing education and there has been no study conducted in Turkey. Aim: This study evaluated the impact of using standardized patients in psychiatric cases on the levels of motivation and perceived learning of the nursing students. Design: This manuscript addressed the quantitative aspect of a doctoral thesis study in which both quantitative and qualitative methods were used. A pre-test and post-test were employed in the quantitative analysis in a randomized and controlled study design. Results: The motivation scores, and interim and post-test scores for perceived learning were higher in the experimental group compared to pre-test scores and the scores of the control group. The students in the experimental group reported that they felt more competent about practical training in clinical psychiatry, as well as in performing interviews with patients having mental problems, and reported less anxiety about performing an interview when compared to students in the control group. Conclusion: It is considered that the inclusion of standardized patient methodology in the nursing education curriculum in order to improve the knowledge level and skills of students would be beneficial in the training of mental health nurses. Highlights: Using standardized patients in psychiatric nursing education had positive impact on motivation and perceived learning of the students. The use of SP methodology provided an enjoyable learning process for the students and increased their participation in the learning process. The students in the experimental group felt themselves more confident in conducting interviews with mentally-compromised individuals.